1996
DOI: 10.1007/bf00048193
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the tropical legume Aeschynomene sensitiva Sw. from root explants

Abstract: Regeneration of Aeschynomene sensitiva Sw. after caUogenesis was obtained from small (2-5 mm long) root explants of 30-day-old seedlings aseptically cultivated on Murashige and Skoog medium supplemented with various concentrations of growth regulators. After 4 weeks, the best results were observed with 0.54 ~ c~-naphthaleneacetic acid and 2.22 BM benzyladenine. On this medium, the rate of regeneration depended on seedling age and agar concentration. The highest number of shoots per explant was obtained with sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…The highest shoot proliferation rates were obtained when calluses were subcultured to fresh regeneration medium containing 5 p,M AgNOs 4 wk after culture initiation (Table 2). Silver nitrate is an inhibitor of ethylene action reported to improve morphogenetic efficiency in several species (Chraibi et al, 1991;Mukhopadhyay et al, 1992;Nef-Campa et al, 1996) and ethylene production is reported to increase in response to stress, including in tissue culture (Mukhopadhyay et al, 1992). The stress caused by the removal of the first shoots could conceivably stimulate ethylene production, with the consequent inhibition of further morphogenesis.…”
Section: Resultsmentioning
confidence: 94%
“…The highest shoot proliferation rates were obtained when calluses were subcultured to fresh regeneration medium containing 5 p,M AgNOs 4 wk after culture initiation (Table 2). Silver nitrate is an inhibitor of ethylene action reported to improve morphogenetic efficiency in several species (Chraibi et al, 1991;Mukhopadhyay et al, 1992;Nef-Campa et al, 1996) and ethylene production is reported to increase in response to stress, including in tissue culture (Mukhopadhyay et al, 1992). The stress caused by the removal of the first shoots could conceivably stimulate ethylene production, with the consequent inhibition of further morphogenesis.…”
Section: Resultsmentioning
confidence: 94%
“…Age of plantlets greatly influenced the regeneration ability of explants excised from garlic root tips, which reached the maximum value (95%) in 15 days old plantlets (Muhammad et al 1997). In addition the highest number of shoots per explant was obtained from 30 days old seedlings in Aeschynomene sensitiva (Claudine et al 1996). Up to the date the effect of planting material with plantlets age on shoot regeneration has not been reported in E. purpurea.…”
Section: Discussionmentioning
confidence: 94%
“…Bud formation from roots is a natural phenomenon observed in some plants, especially under stress conditions. In vitro shoot production from roots can occur spontaneously after long culture periods or be induced by growth regulators, even in those species that do not have this natural ability (Nef-Campa et al 1996;Hosseini-Nasr and Rashid 2002). In Arachis, shoot differentiation from root tissues has already been observed in field conditions (Krapovickas and Gregory 1994) and it was also described in old in vitro cultures of A. villosulicarpa, in response to combinations of NAA and BA (Pittman et al 1984).…”
Section: Resultsmentioning
confidence: 98%